On sign changes of eigenvalues of Siegel cusp forms of genus 2 in prime powers - Das, Soumya; Kohnen, Winfried (Acta arithmetica, 2018)
We prove that under mild assumptions there are infinitely many sign changes in the sequence of eigenvalues of a genus 2 Siegel cuspidal eigenform supported on p^jn for a fixed j >= 1.
Gesehen am 08.02.2019